Vibration energy flow in welded connection of plates - Cieślik, J.; Bochniak, W. (Archives of Acoustics, 2006)
The presented results are concerned with energy transmission in two dimensional plate-likestructures, which undergo the different frequency force excitation. The method for structuralintensity computation is illustrated and formulas of structural intensity for plates and theirrelationship with internal force and strain are given in works [1–4]. The formulas were used inthe program algorithm for structural intensity calculations. The calculations were done withuse the FE method to obtain harmonic response solution. Numerical examples are presented –the welded connection of two flat rectangular plates. The model included the force excitationand dampers formed in lines parallel to the one side of plate and the welded connection. Therelationship between structural intensity and structural mode shapes as well as the changes ofenergy flow in plate for the excitation frequency change are discussed.